The expert and the foreigner: Reflections of forensic transcultural psychopathology on a total of 86 reports by experts on criminal liability. (March 2018) - Merzagora, Isabella; Amadasi, Alberto; Blandino, Alberto; Travaini, Guido
Abstract: In recent times Italy has been experiencing massive migration flows, therefore the attention on the issue of crimes committed by foreigners is increasing. But within trials, in the evaluation of criminal liability of foreigners, how do experts deal with them? Do the performed evaluations take cultural diversity into account? The present study took origin from these questions and examined a total of 86 reports by experts on criminal liability of foreign persons (16 females and 70 males). Examinees have been declared indictable in 31 cases (36%), totally mentally ill in 40 cases (45%) and with diminished liability in 15 cases (17%); when liability was excluded, examinees were diagnosed in 11 cases with mood disorders, in 23 cases with personality disorders, in 4 cases with adaptation disorders and post-traumatic stress disorder and in 10 cases with different diagnoses (in some cases more than one diagnosis was present). None of the reports used the section of the DSM concerning "cultural framing". Tests were used in 48 surveys (56% of cases), with more tests for each examinee, for a total of 39 Rorschach, 14 Raven test, 8 Minnesota Multiphasic Personality Inventory - MMPI - 4 Wechsler Adult Intelligence Scale - WAIS - level test, 8 Thematic Apperception test. When subjects were diagnosed with mental disorder and with diminished liability, 42 (79%) were also socially dangerous. Results highlight the importance of the relationship between the expert and the foreigner. Many factors ought to be critically considered by experts dealing with foreigners, like cultural awareness, knowledge of verbal communication, critical consideration of meanings and diagnosis, knowledge of the foreigners' personal story, presence of tests with inexact information and cultural fallacy.